Effects of comorbidities and functional living activities on survival in geriatric breast cancer patients - Sonmez, Ozlem U.; Arslan, Ulku Y.; Esbah, Onur; Helvaci, Kaan; Turker, Ibrahim; Uyeturk, Ummugul; Budakoglu, Burcin; Bal, Oznur; Oksuzoglu, Berna (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : We evaluated the possible effects of comorbid diseases and functional capacity on the survival of elderly female patients with breast cancer. Material and methods : The study included 159 breast cancer patients aged 65 years or older. Functional status of the patients was evaluated using Katz’s index of activities of daily living (ADL) and Lawton and Brody’s Instrumental ADL (IADL) scale. Results: ADL-based evaluation revealed 121 patients (76.1%) were independent, 34 (21.4%) semi-dependent and 4 (2.5%) dependent whereas IADL-based evaluation showed 69 patients (43.4%) were independent, 67 patients (42.1%) semi-dependent and 23 patients (14.5%) dependent. Among the patients, 69 (43.4%) had one comorbid disease, 62 (39.0%) had two and 26 (16.4%) had three or more. Of the entire cohort, 60.4% received adjuvant chemotherapy. Based on ADL index, overall survival (OS) was significantly better in semi-dependent and independent patients than in dependent patients (p = 0.001). In the upfront non-metastatic patient subgroup, disease-free survival (DFS) was favourable in the independent patients according to ADL index (p = 0.001). Having more than one comorbid disease had an unfavourable effect on OS. In the multiple regression analysis of non-metastatic patients, stage, triple-negative histology and ADL index remained significant in terms of OS (p = 0.008, HR: 3.17, CI: 1.35–7.44; p = 0.027, HR: 2.78, CI: 1.172–6.91; and p = 0.006, HR: 0.29, CI: 0.12–0.70, respectively). Conclusions : In elderly patients with breast cancer, evaluation of daily living activities and comorbid diseases are as important as staging and subclassification of breast cancer in the determination of prognosis and survival.